PATHOLOGICAL CHANGES OBSERVED IN PATIENTS AS A RESULT OF MYOCARDIAL INFARCTION AND METHODS OF EARLY DIAGNOSIS OF THE DISEASE - Akhrorov Abdulaziz Azizjonovich; Kholmatova Mokhinur Abduvokhidovna; Sobirova Dildora Ravshanovna (Western European Studies, 2024)
Myocardial infarction is a pathology that leads to ischemic necrosis of the heart muscle as a result of an acute violation of coronary blood circulation. This is often caused by the formation of blood vessels or, in 90% of cases, severe occlusion of an artery due to atherosclerosis or other factors. Clinically, the disease manifests as burning, squeezing or pinching pain behind the sternum, which can spread to the mouth, neck, scapula and left arm. In this article, the incidence of myocardial infarction in the younger age group, recurrence of the disease, which type of the disease is dominant, and the causes of its origin are considered
Keywords: ECG; coronary angiography; transmural infarction